Long-Term Antithyroid Drug Treatment of Graves’ Disease in Children and Adolescents: A 20-Year Single-Center Experience - Song, Ari; Kim, Su Jin; Kim, Min-Sun; Kim, Jiyeon; Kim, Insung; Bae, Ga Young; Seo, Eunseop; Cho, Young Seok; Choi, Joon Young; Cho, Sung Yoon; Jin, Dong-Kyu (Frontiers in Endocrinology, 2021)
Background/purpose: Graves’ disease (GD) is the most common cause of thyrotoxicosis in children and adolescents. There is some debate regarding the optimal treatment and predicting factors of remission or relapse in children and adolescents with GD. In this study, we report a retrospective study of 195 children and adolescents with GD treated at a single tertiary institution in Korea. Methods: This study included children and adolescents with GD diagnosed before 19 years of age from January of 2000 to October of 2020. The diagnosis of GD was based on clinical features, high thyroxine (FT4), suppressed thyroid-stimulating hormone, and a positive titer of thyrotropin receptor antibodies. Remission was defined as maintenance of euthyroid status for more than six months after discontinuing antithyroid drug (ATD). Results: A total of 195 patients with GD were included in this study. The mean age at diagnosis was 12.9 ± 3.2 years, and 162 patients (83.1%) were female. Among all 195 patients, five underwent thyroidectomy and three underwent radioactive iodine therapy. The mean duration of follow-up and ATD treatment were 5.9 ± 3.8 years and 4.7 ± 3.4 years, respectively. The cumulative remission rates were 3.3%, 19.6%, 34.1%, 43.5%, and 50.6% within 1, 3, 5, 7, and 10 years of starting ATD, respectively. FT4 level at diagnosis (P = 0.001) was predicting factors for remission [HR, 0.717 (95% CI, 0.591 – 0.870), P = 0.001]. Methimazole (MMI)-related adverse events (AEs) occurred in 11.3% of patients, the most common of which were rash and hematologic abnormalities. Of a total of 26 AEs, 19 (73.1%) occurred within the first month of taking MMI. Conclusions: In this study, the cumulative remission rate increased according to the ATD treatment duration. Long-term MMI treatment is a useful treatment option before definite treatment in children and adolescents with GD.